NILAI PENDIDIKAN KARAKTER DALAM KITAB AYYUHAL WALAD SERTA RELEVANSINYA DALAM FILM NEGERI 5 MENARA - Romdloni, Mukhamad (MIYAH : Jurnal Studi Islam, 2024)
Abstract: This research aims to examine the values of character education contained in the book "Ayyuhal Walad" by Imam Al-Ghazali, as well as its relevance to the film "Negeri 5 Menara" directed by Affandi Abdul Rahman. The book "Ayyuhal Walad" is a work that emphasizes the importance of morals, ethics, and ethics in education. Values such as honesty, discipline, responsibility, and love of knowledge are the main focuses that can shape an individual's character. On the other hand, the film "Negeri 5 Menara" depicts the journey of a group of young people who are trying to pursue their dreams in the midst of life's challenges, reflecting the same spirit and values. Through comparative analysis, this study found that the values of character education in "Ayyuhal Walad" are in line with the theme raised in "The Land of 5 Towers". This research divides character education in the book "Ayyuhal Walad" into four parts, namely: (1) character education in becoming the best servant, (2) character education in pursuing knowledge, (3) character education in worship, and (4) character education in maintaining behavior. The four classifications of character education above are found to be relevant in the film Negeri 5 Menara in four different scenes. Keywords: Ayyuhal Walad; Negeri 5 Menara; Character education.